Age-related subniche and aspects of the reproductive biology of Parachondria neglectus (Littorinimorpha: Annulariidae) in Manzanillo, Cuba. - Sariego Frómeta, Sandra; Sariego Tamayo, Orlando Ramón; Marin Morán, Jorge Erick; Lopes de Simone, Luiz Ricardo (Revista de Biología Tropical, 2018)
Parachondria neglectus is a land snail of the Annulariidae family, endemic to Cuba and microlocalized in Granma province. In the present research, the temporal dynamics of age-related subniche and some aspects of the reproductive biology of a P. neglectus population, located in Manzanillo-Granma-Cuba, were characterized. Thirty expeditions were performed from December 2013 to February 2015. The comparisons between the length (t = 8.05, P = 0.007) and biggest diameter (t = 6.24, P = 0.0001) of the shells of truncated juveniles and the shells of full juveniles showed significant statistical differences, indicating that both groups represent two kinds of different ages. The comparison between the biggest diameter of the shells of truncated adults and the shells of full adults (t = 1.50, P = 0.16) showed that both groups represent the same kind of age in the population. The existence of significant statistical differences between the length (t = 19.45, P = 0.0003) and the biggest diameter (t = 13.19, P = 0.006) of the females’ shells and the males’ shells verify the sexual dimorphism in the species, proving to be the females of bigger dimensions in relation to the males. The whitish circular spot in the shells is a valid external morphological characteristic to differentiate the adult females already mated in previous occasions from the rest of the members of the population. The reproductive period was from July to December 2014. Copulations were observed from July to October 2014 and they were associated to conditions of abundant precipitations and high temperatures of summer. The recruitment period took place from September to December 2014.